The Effectiveness of A Reproductive Health Active Learning Process Model in Improving Teen's Knowledge and Self-Trust in the First Middle School - Teresia Retna P; Wahyuningsih Triana Nugraheni (Journal of Global Pharma Technology, 2020)
Adolescence is a transitional period between childhood and adulthood, which begins at the time of sexual maturity, namely between the ages of 11 or 12 years to 20 years, namely before young adulthood (Soejiningsih, 2004). To be ready to enter adulthood, adolescents begin to get acquainted and deal with various adult problems. Biologically, adolescents already have the ability like adults, but psychologically they have not got the right to use these abilities. The occurrence of psychological changes causes confusion among adolescents. They experience emotional turmoil and mental stress so that they easily deviate from the rules and social norms that apply in society. The design of this study was an experiment with a Posttest Only Control Group Design approach. In the experimental design of this study, there were two groups selected randomly. One group acts as a control group and the other group acts as an experimental group. The population in this study were students of health cadres at SMP Negeri 1 Merak Urak, Tuban Regency in 2019/2020, with a sample size of 36 students. The sample of this research was some students of health cadres at SMP Negeri 1 Merak Urak, Tuban Regency, with a sample size of 33 students. The sampling technique used was simple random sampling. The independent variable of this research is the active learning process of adolescent reproductive health, the dependent variable of this study is the level of knowledge and self-confidence of adolescents. The research instrument used in this study was to use a modified adolescent reproductive health active learning process module and a questionnaire to measure the level of knowledge and self-confidence of adolescents in junior high school. Data analysis was used to determine the effect of the independent variable and the dependent variable with the Manova test, with an error rate of α 0.05. Hypothesis testing shows that the significance value for the treatment and control groups tested by the Pillai Trace, Wilk's Lamda, Hotteling's T and Roy's Largest Root procedures is 0.005